Spatial concepts of the work environment - Schnotale, Grzegorz (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2018)
Technological changes and universal digitization have a significant impact on shaping the architectural environment of work, study and innovation. The article discusses the subject of determinants of the spatial concept of the work environment based on BMW office buildings in Munich, Germany. Based on selected examples of office buildings in Munich from the 1960s and contemporary implementations, an attempt was made to describe the factors affecting the functioning of the office work environment and its organization.